First Five Year Plan Bombay State East Khandesh District - Government of Bombay (Government of Bombay, 1954)
The First Five-Year Plan (1951-52 to 1955-56) for East Khandesh District presents a comprehensive strategy aimed at socio-economic growth, with a strong focus on agriculture, education, health, and rural development. Agricultural initiatives emphasized the expansion of cultivated areas, improved crop varieties, and the distribution of fertilizers, while irrigation projects, including minor and major works, enhanced water accessibility and crop productivity. Education efforts expanded primary schooling, increased teacher training facilities, and established hostels for backward class students, ensuring broader access to quality learning. Health programs integrated rural clinics, ambulance services, preventive malaria measures, and the transformation of dispensaries into cottage hospitals. Infrastructure development, particularly in transportation, facilitated connectivity through roads and highways, directly supporting trade and industrial activities. Cooperative societies proliferated to provide agricultural credit, marketing support, and community involvement in economic decisions. Special attention was given to backward classes through free education, economic support via loans and subsidies, minimum wage protections for forest laborers, interest-free housing loans, job reservations, and grants to NGOs working for social upliftment. Community development projects prioritized local participation in constructing water supply systems, sanitation facilities, and small infrastructure projects, fostering self-sufficiency and communal engagement. Overall, the plan reflects a structured approach to sustainable growth, integrating economic, social, and educational initiatives with targeted support for marginalized populations, thereby laying a foundation for long-term development aligned with state and national objectives.
East Khandesh District
East Khandesh District
Keywords: East Khandesh District; State Five Year Plan; Agricultural Development; Irrigation Projects; Education Initiatives; Health Services; Rural Development; Transportation Infrastructure; Cooperative Societies; Backward Classes; Housing Schemes; Community Development